2021
DOI: 10.1371/journal.pntd.0009156
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 in end-stage renal disease patients with renal replacement therapies: A systematic review and meta-analysis

Abstract: Background The novel coronavirus (COVID-19), caused by SARS-CoV-2, showed various prevalence and case-fatality rates (CFR) among patients with different pre-existing chronic conditions. End-stage renal disease (ESRD) patients with renal replacement therapy (RRT) might have a higher prevalence and CFR due to reduced immune function from uremia and kidney tropism of SARS-CoV-2, but there was a lack of systematic study on the infection and mortality of the SARS-CoV-2 infection in ESRD patients with various RRT. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 64 publications
2
17
1
Order By: Relevance
“…This possibility is supported by the policy of some hospitals such as the university hospital of Geneva (HUG), where many patients who died from COVID-19 would not have been admitted to an ICU because of local triage criteria ( 6 ). Our findings, again, are supported by the above mentioned review and meta-analysis ( 12 ), which showed that ESRD patients have a 3.6 times higher risk of dying than the general population in the first wave.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This possibility is supported by the policy of some hospitals such as the university hospital of Geneva (HUG), where many patients who died from COVID-19 would not have been admitted to an ICU because of local triage criteria ( 6 ). Our findings, again, are supported by the above mentioned review and meta-analysis ( 12 ), which showed that ESRD patients have a 3.6 times higher risk of dying than the general population in the first wave.…”
Section: Discussionsupporting
confidence: 89%
“…Third, contact with health care workers is also a potential source of transmission, what is supported by the fact that patients on 1–2 dialysis sessions per week or on PD were tested less often positive for SARS-CoV-2 than patients on thrice-weekly dialysis schedules ( Table 6 ). A systematic review and meta-analysis from the first wave from Nopsopon et al ( 12 ) supports our findings with end-stage renal disease (ESRD) patients getting tested positive much more often than the general population.…”
Section: Discussionsupporting
confidence: 83%
“…The COVID-19 pandemic has been particularly challenging for vulnerable patients receiving HD. A meta-analysis (15 studies, 20,671 participants) reported that the prevalence of COVID-19 among patients on KRT was 3.1% (95% CI 1.3%–5.7%) and the mortality rate was 18.1% (95% CI 14.1–23.3) 99 . Of note, these prevalence and mortality rates vary according to community transmission rates at the time.…”
Section: Clinical Hd Outcomes Across the Globementioning
confidence: 99%
“…When compared to general population, COVID‐19 has high mortality in end‐stage renal disease (ESRD) 1 patients. Prevention of virus spread among ESRD patients is of paramount importance.…”
Section: Introductionmentioning
confidence: 99%